No interaction effect between Interleukin-6 polymorphisms and acid ash diet with bone resorption marker in postmenopausal women - Lim, Sook Yee; Chan, Yoke Mun; Ramachandran, Vasudevan; Mohd Shariff, Zalilah; Chin, Yit Siew; Arumugam, Manohar (MDPI, 2021)
: Background: Evidence is growing that a high-acid diet might accelerate the rate of bone loss, and gene polymorphisms such as Interleukin 6 (IL6) -174G/C and -572G/C are related to bone deterioration. However, no study of the interaction between diet and IL6 polymorphisms has been conducted among Asians. Thus, the objective of this study was to determine whether IL6 gene polymorphisms modified the association between dietary acidity and the rate of bone resorption. Methods: This cross-sectional study recruited 203 postmenopausal women (age ranged from 51 to 85 years old) in community settings. The dietary intakes of the participants were assessed using a validated interviewer-administered semi-quantitative food frequency questionnaire (FFQ), while dietary acid load (DAL) was estimated using net endogenous acid production (NEAP). Agena® MassARRAY genotyping analysis and serum collagen type 1 cross-linked C-telopeptide (CTX1) were used to identify the IL6 genotype and as a bone resorption marker, respectively. The interactions between diet and single-nucleotide polymorphisms (SNPs) were assessed using linear regressions. Results: A total of 203 healthy postmenopausal women aged between 51 and 85 years participated in this study. The mean BMI of the participants was 24.3 kg/m2 . In IL6 -174 G/C, all the participants carried the GG genotype, while the C allele was absent. Approximately 40% of the participants had a high dietary acid load. Dietary acid load (B = 0.15, p = 0.031) and the IL6 -572 CC genotype group (B = 0.14, p = 0.044) were positively associated with a higher bone resorption. However, there was no moderating effect of the IL6 genetic polymorphism on the relationship between and acid ash diet and bone resorption markers among the postmenopausal women (p = 0.79). Conclusion: High consumption of an acid ash diet and the IL6 -572 C allele seem to attribute to high bone resorption among postmenopausal women. However, our finding does not support the interaction effect of dietary acidity and IL6 (-174G/C and -572G/C) polymorphisms on the rate of bone resorption. Taken together, these results have given scientific research other candidate genes to focus on which may interact with DAL on bone resorption, to enhance planning for preventing or delaying the onset of osteoporosis among postmenopausal women.